CSIG-32. microRNA 211, A POTENTIAL THERAPEUTIC AGENT FOR GROUP 3 MEDULLOBLASTOMA IN CHILDREN. (12th November 2021) - Katsushima, Keisuke; Lee, Bongyong; Yuan, Menglang; Kunhiraman, Haritha; Stapleton, Stacie; Jallo, George; Raabe, Eric; Eberhart, Charles; Perera, Ranjan
Abstract: Medulloblastoma (MB) is a central nervous system (CNS) tumor that predominantly affects children and requires aggressive therapy. Affected individuals often suffer from treatment-related side-effects and treatment-resistant recurrences associated with high morbidity and mortality rates. There are four major molecular MB subgroups: wingless-type (Wnt)-activated, sonic hedgehog (Shh)-activated, group III (G3), and group IV (G4) MBs. While the molecular pathology of Wnt- and Shh-activated MBs is well defined, rather less is known about G3 and G4 MB's genetic basis, so their molecular diagnosis and consequent management have remained challenging. MBs develop through various genetic, epigenetic, and non-coding (nc)RNA-related mechanisms, with the role of ncRNAs, particularly microRNAs, in MB tumor growth is poorly defined. We addressed this knowledge gap with an exemplar of microRNA-211 (miR-211) implicated in G3 MB tumor growth. Compared to other MB subgroups, miR-211 is significantly downregulated in G3 MB cell lines, underscoring its important role as a therapeutic agent and a biomarker. miR-211 overexpression in G3 MB cells significantly reduced cell proliferation, invasion, 3D colony formation, and induced apoptosis. Oxygen consumption rates are higher in engineered cells, and we postulate that miR-211 is involved in G3 MB mitochondrial energy metabolism. miR-211 expressed G3 MB cells injected into mouse cerebella produce smaller tumors than those derived from parental cells. We applied single-cell RNA sequencing and immune histochemical assays to characterize tumors to identify the molecular mechanism of miR-211 - driven tumor reduction in G3 MBs, and our preliminary results support that miR-211 is an attractive therapeutic agent to treat this aggressive MB subtype.